The Relationship Between Peer Group Support and Snack Choosing Behavior Among School-Aged Children at Limboto 1 Public Elementary School - Stevilia Marcella H. Djafar; Ridha Hafid; Rini Wahyuni Mohamad (Medical and Health Journal, 2026)
School-age children, aged 6 to 12, are at a crucial developmental stage, where school experiences are a key aspect of their lives. Children's snack selection behavior is influenced by two factors: personal factors such as knowledge and habits, and environmental factors such as the role of family, peers (peer group), and school conditions. Peer group support is a form of social support provided by individuals within friendships to help and strengthen each other. This study aims to determine the relationship between peer group support and snack choice behavior among school-aged children at Limboto 1 Public Elementary School. This study used probability sampling, a technique that provides an equal opportunity for each member of the population to be selected as a sample. The method used in this study was proportionate stratified random sampling, a sampling technique used when the population has non-homogeneous members and is divided into strata with varying numbers. The results above indicate a relationship between peer group support and snack choice behavior among school-aged children. This was confirmed by statistical testing using Chi Square, which yielded a p-value of 0.009 <α = 0.05.